Pyroptosis drives CD4 T-cell depletion in HIV-1 infection - Doitsh, Gilad (2014)
The pathway causing CD4 T-cell death in HIV-infected hosts remains poorly understood. Apoptosis has been proposed as the key mechanism for CD4 T-cell loss. We now show that caspase-3-mediated apoptosis accounts for the death of only a small fraction of productively infected cells. The remaining >95% of quiescent lymphoid CD4 T-cells die by caspase-1-mediated pyroptosis triggered by abortive viral infection. Pyroptosis corresponds to an intensely inflammatory form of programmed cell death where cytoplasmic contents and pro-inflammatory cytokines including IL-1β, are released. This death pathway thus links the two signature events in HIV infection––CD4 T-cell depletion and chronic inflammation––and creates a vicious pathogenic cycle where dying CD4 T-cells release inflammatory signals that attract more cells to die. This cycle can be broken by caspase-1 inhibitors shown to be safe in humans, raising the possibility of a new class of “anti-AIDS” therapeutics targeting the host rather than the virus.